The effect of different irrigation techniques on the quality of cleaning of root canal walls - Pavlović Violeta; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2008)
Aim: To evaluate the effect of irrigation techniques, i.e. different types of irrigation needles, on the quality of cleaning of root canal walls using scanning electron microscopy (SEM). Material and Method: The study was conducted on 16 extracted, single-rooted, human teeth. The samples were allocated to two experimental groups depending on the type of the irrigation needle. Conventional needles were used for the irrigation of Group I and laterally perforated ones for Group II. All root canals were instrumented using K files and the Step-back technique. During instrumentation, all samples were irrigated with 2.5 % sodium hypochlorite solution followed by final irrigation with 17 % EDTA for 1 min. After that, all samples were irrigated with 10 ml of distilled water. The roots were, then, sectioned longitudinally and middle one third of each root canal was analyzed using SEM. Quantitative analysis was based on criteria by Hülsmann et al. Results: The obtained results showed that the more efficient removal of debris and the smear layer was accomplished in the group of samples irrigated using laterally perforated needles than conventional needles. The difference between the investigated irrigation techniques were statistically significant (p<0.01). Conclusion: The use of laterally perforated needles for irrigation allows more efficient cleaning of root canal walls, i.e. the removal of debris and the smear layer.